MANAJEMEN KELAS CERDAS ISTIMEWA (Studi Kasus di Sekolah Menengah Atas Negeri 2 Bantul) (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This research aims to describe the management of the gifted class of learning in SMA N 2 Bantul which was conducted by teachers which include: (1) lesson planning, (2) learning organization, (3) the implementation of learning, and (4) assessment of learning. This is qualitative research. SMA N 2 Bantul was choosing as the research site because only this school which hold this program in Bantul. Data collection was conducted by means of observation, interview, and documentation.The result of the research shows that: (1) the planning of student recruitment process was well conducted and based on particular requirements and the planning of learning process was conducted by the school including: the making of learning administration, the planning of learning materials, the planning of teaching methods, the media used is well planning, the planning of evaluation is as the rule, (2) The organization of gifted class including learning materials and teacher organization has been well conducted like the guidance. (3) The implementation of the learning process has achieved the target, (4) The assessment to students learning needs some improvement maximally, not only in tested but also non-tested technique. It need evaluation related to the implementation giftedprogram by asking and giving suggestion from any experts or resources, so, in future, the implementation can be running optimally.